Analysis of a small-scale reactor core with PARCS/Serpent. (July 2018) - Fejt, F.; Frybort, J.
Abstract: Cross section homogenization is a challenging task that has been implemented mainly for full-core calculations of nuclear power plants. Small-scale reactors started to be a main point of interest for this kind of analysis during last few years. This paper presents a suitable homogenization strategy for a small core of VR-1 reactor (28.6 × 28.6 cm) realized by Serpent 2.1.28. Homogenized macroscopic data are used in PARCS_v3.2 core simulator for calculations of multiplication factor and radial flux distribution in the core. The PARCS results are compared to reference results calculated by Serpent 2.1.28. Reasons for observed inconsistencies between these two calculation modes are discussed.